2013
DOI: 10.1007/s10856-013-4982-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of magnesium implantation on the osteomyelitis modeled animals induced by Staphylococcus aureus

Abstract: Pure magnesium (Mg) granules were implanted into the tibial medullary cavity of osteomyelitis modeled animals after debridement, and the animals without implant were taken as the control group. The antibacterial and osteogenic effects on bone tissue during Mg degradation were evaluated through detecting Mg ions, counting bacteria culture in peripheral blood, histology and iconography. The results showed that there was no significant difference for the concentration of serum Mg between the preoperative and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Even though in vivo antibacterial effects as well as pH increases have been reported, in our murine model magnesium implants showed only a modest reduction in bacterial activity but could not eliminate infections after implantation. 6,7,41 Conceivably, this may have been due to the brief contact of the bacteria to magnesium during the surgical procedure while after implantation the dispersal of the bacteria in the surrounding tissue, a limited magnesium corrosion rate and the buffering capacity of the living tissue could have contributed to prevent the generation of bactericidal pH levels. A physiological pH at the magnesium-tissue interface would be in line with the biocompatible behavior of magnesium implants in numerous animal models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though in vivo antibacterial effects as well as pH increases have been reported, in our murine model magnesium implants showed only a modest reduction in bacterial activity but could not eliminate infections after implantation. 6,7,41 Conceivably, this may have been due to the brief contact of the bacteria to magnesium during the surgical procedure while after implantation the dispersal of the bacteria in the surrounding tissue, a limited magnesium corrosion rate and the buffering capacity of the living tissue could have contributed to prevent the generation of bactericidal pH levels. A physiological pH at the magnesium-tissue interface would be in line with the biocompatible behavior of magnesium implants in numerous animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective applications for degradable metallic implants in soft tissue are vascular stents to keep blood vessels open until newly formed vessels can overtake their function or in hard tissue, screws or nails to stabilize broken bones until the healing process is completed. Advantages of magnesium alloys that have been reported include bone regenerating, non‐inflammatory as well as antibacterial properties . Such inherent antibacterial activities of implants could antagonize the formation of antibiotic treatment‐resistant bacterial biofilm infections and would therefore be highly relevant .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a promising alternative to insufficient systemic antibiotic treatments antibacterial implants could temporarily achieve highly effective local antibiotic concentrations without causing systemic side effects . Interestingly, antibacterial properties of magnesium alloys and of pure magnesium have been documented both in vivo and in vitro and it correlated with pH increases . By employing genetically engineered bioluminescent S. aureus and P. aeruginosa strains we have recently demonstrated that alkalization is both necessary and sufficient for the antibacterial effects of corroding magnesium in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in previous investigations, the corrosion products of Mg were found to possess an in vitro antibacterial function due to the increase in the local alkalinity caused by Mg degradation. 6,7 These favourable properties of Mg based metals suggest that they could be clinically used as a novel kind of orthopaedic implants, which have great potential for prevention of implant associated infections. However, pure Mg seems suitable not to be directly used as implant material due to its fast degradation and lower strength, so the composite coatings are generally coated in order to control their degradation rate.…”
Section: Introductionmentioning
confidence: 99%